REVIEW DESIGN LERENG GALIAN DENGAN PERKUATAN GEOGRID PADA PROYEK JLS LOT 6 TULUNGAGUNG STA 12+625 - Afidia, Nadsya Qanita; Dandung Novianto; Moch. Sholeh (Jurnal Online Skripsi Manajemen Rekayasa Konstruksi (JOS-MRK), 2023)
Slope in STA 12+625 JLS LOT 6 project, the existing desain was 1:1 slope unreinforced with 30 m height, reviewing design with geogrid as slope reinforcement using soil parameter SPT data as calculation data. The calculation of slope stability using Bishop Simplified Method and analyzed the sliding pattern using the GeoStudio SLOPE/W program, taking into account the earthquake load which refers to SNI 1726:2019. Calculation of the cost plan uses the analysis of the unit price of the Tulungagung Regency 2020.The analysis result showed the pullout safety factor is 2,16, safety factor against sliding failure each are ,57 , 1,73 and 1,89 for geogrid with 20 m, 22 m, 24 m length, safety factor againts deep-seated global stability is 4,95 and safety factor againts landsliding without earthquake load is 1,51. The cost plan for the reinforced slope with geogrid as the reinforcement is Rp. 4.423.105.139,-.